Assessing the Relationship Between Religiosity and Recidivism Among Adult Probationers in Pakistan - Bhutta, Mazhar H. (International journal of offender therapy and comparative criminology, 2019)
Although empirical evidence supports a relationship between religiosity and criminal behavior, debate continues about the theoretical mechanisms by which they are related. Moreover, the topic has been largely ignored by practicing clinicians and correctional workers. The Muslim Religiosity-Personality Inventory: Abridged was administered to low-risk Pakistani probationers and factor analyzed, after which probationers' recidivism was monitored. Five oblique factors were obtained, three of which were correlated with recidivism (Religious Practice, Religious-Moral Values, and Fundamental Religious Beliefs), as was the full scale, while two were not (Importance of Religion and Rejection of Nonbeliever). In a logistic regression, Religious-Moral Values and Religious Practices contributed to the prediction of probationer recidivism. However, when demographic characteristics were introduced, education and marital status replaced Religious Practices. This study supports the religiosity-crime link in a non-Western, Muslim culture. Implications for assessing religiosity and for practitioners in the justice system are discussed.